Knowledge, attitudes, and practices regarding emergency contraception pills among adult students within the college of medical sciences, University of Guyana, from August to September 2024 - Howard, Nickalus; Sukdeo, Nirvanie A.; Bess, Tinesha D.; Mentore, Tanesha R. A.; Gobin, Leonardo; Stewart, Jonnell S.; Smith, Pretha D.; Low, Guy; Jones, Quincy; Gobin, Reeta; Surujpaul, Petal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Emergency contraceptive pills (ECPs), commonly known as the morning-after pill, are used to prevent unplanned pregnancy after unprotected intercourse, sexual assault, or failure of regular contraception. This study aimed to assess the knowledge, attitudes, and practices of ECPs among adult students from the College of Medical Sciences (CoMS). Methods: A cross-sectional descriptive study was conducted at the University of Guyana, Turkeyen Campus, between August and September 2024. Data was collected through a structured electronic questionnaire and analyzed using descriptive methods, and the chi-square test for statistical significance. Results: Out of 321 respondents, 76.1% were females and 23.6% were males, with a mean age of 23 years. 57% were from region 4, and 69.8% were Christians. The study found that the majority of students (86.6%) had adequate overall knowledge about ECPs, but there were notable gaps in understanding specific aspects, including mechanisms of action, side effects, and optimal timeframe for use. The study also found that attitudes toward ECPs were mixed, with a significant proportion of students holding negative attitudes (51.7%). However, the majority of students (95.5%) reported that ECPs were easy/very easy to obtain, and most students reported that they were somewhat effective (68.8%). Conclusions: This study highlights the importance of targeted educational interventions to address knowledge gaps and misconceptions regarding ECPs. The findings have implications for the development of comprehensive sexual health education programs and policies aimed at promoting safe sexual practices and reproductive health among university students in Guyana.